2017
DOI: 10.1111/codi.13600
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled trial comparing early postoperative complications in patients undergoing loop colostomy with and without a stoma rod

Abstract: The stoma rod does not prevent stomal retraction. However, complication rates are significantly higher when a stoma rod is used. Routine use of a stoma rod for construction of loop colostomy can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
8
0
4
Order By: Relevance
“…1. A total of 1131 patients were included in 6 studies [9][10][11][12][13][14], including support rod group (n = 569) and non-support rod group (n = 562). All patients were followed up for more than 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. A total of 1131 patients were included in 6 studies [9][10][11][12][13][14], including support rod group (n = 569) and non-support rod group (n = 562). All patients were followed up for more than 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…It was not specified length of the rod that has been placed in the study of Zindel et al [13]. The duration of rod use was short being only 3.5 days in the study of Whiteley et al [11], but in another two studies [9,14], the rod was removed on the 7-8th day after surgery, while in the RCT performed by Franklyn et al [12], the rod was left in place until the 10-14th day after surgery, and even more, according to the study of Oh et al [10], the rod was braced until the 4-28th day after surgery. Three studies reported length of stay, and sufficient data was available in two of three studies for inclusion in the meta-analysis.…”
Section: The Length Of Placement Of Stoma Rod and Hospital Staymentioning
confidence: 99%
“…Após a aplicação dos demais critérios de inclusão, dos 29 estudos selecionados para a leitura na íntegra, 19 compuseram a amostra da presente revisão, conforme mostra o fluxograma na Figura 1. Dos 19 estudos incluídos na revisão [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] , quatro foram desenvolvidos na Holanda, três nos Estados Unidos da América, dois na Índia, dois na China, dois na Noruega, um na Finlândia, um no Japão, um na Arábia Saudita, um na Turquia, um na Alemanha e um no Irã. O Inglês foi o idioma da totalidade dos estudos.…”
Section: Resultsunclassified
“…Na categoria técnicas cirúrgicas foram vinculados 10 artigos [9][10][11][12][13][14]17,19,20,24 que estudaram o manejo de complicações de estomia e pele periestoma. Esta categoria fornece ao profissional subsídios para o desenvolvimento de estratégias de cuidados pré e pós-operatórios relacionados às diversas técnicas cirúrgicas e suas consequências.…”
Section: Técnicas Cirúrgicasunclassified
See 1 more Smart Citation